Sustainable and eco-friendly syntheses of green MXenes for advanced battery applications - Seonju Kim; Hyeonmin Jo; Jiyoung Yun; Jun-Won Lee; Jiung Cho; Kisuk Kang; Hee-Dae Lim (Nano Convergence)
Abstract MXenes, a versatile family of two-dimensional (2D) transition metal carbides and nitrides, have attracted significant attention for battery applications due to their exceptional properties, such as high electronic conductivity, tunable microstructure, robust mechanical and chemical stability, and compositional diversity. However, despite these advantages, conventional MXene synthesis methods-relying heavily on toxic acid etching-pose serious environmental hazards, undermining their suitability for sustainable energy applications. In this context, eco-friendly and non-toxic MXene synthesis routes have become increasingly critical for enabling the widespread adoption of MXene, driving extensive research into alternative, green synthetic approaches. These recent advances in environmentally benign synthesis are pivotal to unlocking the full potential of MXenes for diverse next-generation battery technologies. In this review, we provide a comprehensive overview of green and sustainable MXene synthesis strategies, highlighting the latest developments that go beyond traditional fluorine-based routes. Each synthetic process is comparatively analyzed with respect to its efficacy, limitations, and implications for practical application as key functional components in lithium-ion batteries (LIBs) and post-LIB systems. Finally, we offer a perspective on how the development of eco-friendly MXenes can contribute to overcoming the industrial challenges facing advanced battery technologies. Graphical Abstract